The Utilization Interactive Digital Media Comic In Indonesian Historical Learning to Support Independet Learning at SMA Al-Izzah - Moch. Dimas Galuh Mahardika; Nur Wahyu Putra (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The development of technology in the era of industrial revolution 4.0 has a comprehensive impact into aspects of life, one of which is in the learning of history. The use of electronic media for historical learning needs has begun to be encouraged in various schools. Conventional historical learning is usually still one-way, or in other words still teaching oriented. Thus with the development of technology and to meet the needs of the times, learning media needs to be used in order to improve the quality of learning. In addition, with the use of learning media, it is expected that students have an interest in participating more in historical learning. This research tries to review the use of digital comic learning media in the subjects of Indonesian History in class X- MIA 3 senior high school Al-Izzah Kota Batu. The research method used a descriptive qualitative method.